Diagnostic challenges and therapeutic implications of Hyperostosis Frontalis Interna (HFI) in a post-menopausal woman - A case report - Prabhudev M Hiremath; Anish Mehta; Rakshith Srinivasa; Pradeep R; Mahendra Javali; R Srinivasa (Romanian Journal of Neurology, 2024)
This case report highlights the importance of recognizing Hyperostosis Frontalis Interna (HFI) in patients with a diverse clinical presentation, particularly in post-menopausal individuals with relevant risk factors. It emphasizes the need for maintaining a high index of suspicion in neurological settings. Timely identification and treatment of HFI can significantly improve patient outcomes and alleviate debilitating symptoms and comorbidities. HFI, often an under-diagnosed condition and an incidental radiological finding, calls for ongoing research and vigilance in clinical practice.